The inhibitory effect of some nanoparticles on biofilm formation of Streptococcus agalactiae - Abdul-Hamza, Haneen kadhum; Mohammed, Ghaidaa Jihadi (Al-Qadisiyah Journal of Pure Science, 2019)
: Biofilm are a link between microorganisms in which germ cells stick together on living or non-living surfaces within a self-produced polymer